Exploring the Nature and Extent of Employment among Female Agricultural Workers in Haryana. (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
This research paper investigates the nature and extent of employment among female agricultural workers in Haryana to illuminate their roles, employment patterns, and awareness of labour rights. Addressing a critical gap in understanding the socio-economic conditions of female cultivators and labourers, the research focuses on their participation in various agricultural activities, wage disparities, and challenges. A comprehensive survey was conducted across three districts—Rewari, Karnal, and Rohtak—utilizing cluster sampling to select a representative sample of 422 female agricultural workers. Data collection involved structured interviews and questionnaires, capturing detailed information on employment patterns, awareness of labour rights, and socio-economic conditions. Statistical analyses were employed to interpret the data, including participation indices and descriptive statistics. The study reveals significant engagement of female agricultural workers in essential tasks such as harvesting, weeding, and post-harvest processing, yet highlights their limited participation in activities like irrigation and field preparation. Alarmingly, awareness of "equal pay for equal work" remains critically low, with only 5.24% of cultivators and 4.02% of laborers familiar with the principle. This indicates a pervasive gap in knowledge that exacerbates gender-based wage disparities. The findings highlights the indispensable contributions of female agricultural workers while highlighting the urgent need for targeted interventions to address wage inequality and improve working conditions. Enhancing awareness of labour rights through education and policy measures is crucial for fostering equitable and sustainable agricultural practices. Future research should continue exploring strategies for empowering female agricultural workers and ensuring their inclusion in rural communities' economic and social fabric.